Morphometry Dynamical of Siombak Lake, Medan Indonesia - Ahmad Muhtadi; Zulham Apandy Harahap; Rusdi Leidonald (Journal Omni-Akuatika, 2017)
Siombak lake (28 ha area) was a salty lake located in Medan coastal, Indonesia. Water fluctuation influenced by the sea tide. Therefore, it needed to do morphometry dynamical study as the first impression of lake physical characteristic. The purpose of this study was to understand the dynamical of Siombak lake morphometry. The research was done in September 2016. Lake mapping was done by making 100 line zig zag and draw with ArcMap. Bathymetry showed that the bottom of the lake was sloping at the center part of west and southeast of the lake, and steeping at north, south and east. Siombak Lake has shoreline length 2,535.78 m, with SDI value 2.70. Maximum length 756 m, with maximum width 246.15 m. Lake maximum depth was 17.7 m at MSL, 18.98 m at highest tide and 16.71 m at lowest tide, with average depth 5.33 m at MSL, 6.30 m at highest tide and 4.30 m at lowest tide. Lake volume was 783,607.16 m3 at MSL, 829,395.52 m3 at highest tide and 355,544.14 m3 at lowest tide, with water debit around 32.50 – 50.17 m3s-1. Water retention time was ± 4.33 – 6.75 hours